PERLINDUNGAN HUKUM TERHADAP KEKERASAN SEKSUAL PADA ANAK MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Absi, Warmiyana Zairi; Novianti, Sella; Pertiwi, Bella (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Abstract Sexual violence is a legal issue that is very important to study because in this case it involves the human rights of victims which result in traumatic psychological and physical trauma. The phenomenon of sexual violence against children in Indonesia has a problem. Sexual violence in Indonesia continues to increase significantly. However, many victims of sexual violence against children do not have the courage to report to the obligatory parties or child protection agencies about criminal acts of sexual violence. The above is what motivated the writer to be interested in writing this thesis and research. This research aims to find out how far the application and protection of the law against sexual violence against children in the city of Palembang Law No. 35 of 2014 concerning amendments to Law No. 23 of 2002 About Child Protection. In this study the authors used qualitative research. The research method used is an empirical juridical research method with data collection techniques through library research and field studies, namely conducting direct interviews with related parties. From the results of this study it will be known how the implementation of